Postfeminist Whiteness Problematising Melancholic Burden in Contemporary Hollywood - Marston, Kendra (Edinburgh University Press, 2018)
Kendra Marston interrogates representations of melancholic white femininity in contemporary Hollywood cinema, arguing that the 'melancholic white woman' serves as a vehicle through which to explore the excesses of late capitalism and a crisis of faith in the American dream.